Standardization and Digitalization of Buddhist Marriage Guidance: Addressing Implementation Inconsistencies and Low Program Efficacy - Yon Hasa (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper discusses the quality of Buddhist Marriage Guidance, which is currently not optimal in equipping prospective brides and grooms with an understanding of Dhamma principles and practical skills for fostering harmonious families. The main policy issue is the severe inconsistency in implementation and curriculum, triggered by weak binding national regulations and a policy focus that is too administrative rather than substantive program outcomes. Through descriptive qualitative methods, in which the author analyzes this issue using public policy theory approaches (such as Standardization Theory, Implementation Failure, and Result-Oriented Administration) and supported by an USG (Urgency, Seriousness, Growth) analysis for problem priority, it is found that the root of the problem lies in the failure of the oversight system to address the high autonomy of the Assembly and resistance to standardization. The USG analysis identifies five main problems, with three of the top priorities: Curriculum Inconsistency, Unstandardized Facilitators, and Cross-Sector Synchronization (Scores 13-14). Therefore, this policy paper recommends the issuance of a Decree of the Director General of Buddhist Community Guidance on the Establishment and Management of a Centralized Digital Platform. This decision was chosen based on William N. Dunn's scoring, which showed that the digital solution achieved the highest score (22) because it was considered the most efficient and capable of ensuring equal access to the Minimum Core Curriculum to all Buddhists, fundamentally shifting the focus from fulfilling administrative requirements to achieving substantive results in the form of increasing program efficacy and the quality of Buddhist families in Indonesia.